2021
DOI: 10.3389/fcell.2021.673599
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoregulation of YAP and TAZ in Cellular Homeostasis and Disease Progression

Abstract: Biophysical cues, such as mechanical properties, play a critical role in tissue growth and homeostasis. During organ development and tissue injury repair, compressive and tensional forces generated by cell-extracellular matrix or cell-cell interaction are key factors for cell fate determination. In the vascular system, hemodynamic forces, shear stress, and cyclic stretch modulate vascular cell phenotypes and susceptibility to atherosclerosis. Despite that emerging efforts have been made to investigate how mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 133 publications
(176 reference statements)
1
129
0
Order By: Relevance
“…Furthermore, YAP binds to transcriptional enhanced associate domain (TEAD) in the nucleus, which affects target gene such as CTGF and then cell proliferation and differentiation, tissue regeneration and organ size determination (Zhang et al, 2014;Brusatin et al, 2018). It has been reported that increased ECM stiffness activates YAP, which leads to ECM deposition and then contributes to increased ECM stiffness (Cai et al, 2021). Despite these important findings, the molecular mechanisms by which MCs sense and transduce the mechanical signals to activate YAP needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, YAP binds to transcriptional enhanced associate domain (TEAD) in the nucleus, which affects target gene such as CTGF and then cell proliferation and differentiation, tissue regeneration and organ size determination (Zhang et al, 2014;Brusatin et al, 2018). It has been reported that increased ECM stiffness activates YAP, which leads to ECM deposition and then contributes to increased ECM stiffness (Cai et al, 2021). Despite these important findings, the molecular mechanisms by which MCs sense and transduce the mechanical signals to activate YAP needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, RhoA feels high ECM stiffness through focal adhesion, promotes actin polymerization and stress fiber formation, transmits stiffness signals to YAP/ TAZ, and regulates the sensitivity of osteoblasts (Wagh et al, 2021). MRTF and YAP/TAZ have been confirmed as transcription factors activated by mechanical induction (Finch-Edmondson and Sudol, 2016;Cai et al, 2021). The activity of ROCK is positively correlated with ECM stiffness.…”
Section: Rhoa Signaling Pathwaymentioning
confidence: 98%
“…One of the most characterized mechanosensitive pathways is the Hippo pathway and its components YAP and TAZ that interact with FA [ 36 , 37 ]. Another mechanosensitive sensor and transducer of mechanical stress is the calcium-permeable Piezo channel [ 38 ], located at the plasmatic membrane, which can assist the cell in choosing the migration pattern under a certain level of pressure and can shift movements using blebs rather than pseudopods [ 39 ].…”
Section: Mechanical Stress During Metastasismentioning
confidence: 99%